Violência provocada pelo parceiro íntimo: prevalência e fatores associados em usuárias da atenção primária à saúde em região metropolitana de Belo Horizonte, Minas Gerais, Brasil - Doriana Ozolio Alves Rosa (2013)
The violence is now one of the biggest health problems in the world: 1.6 million deaths / year and more than 16 million hospitalizations / year are associated with violence. This situation, though serious, is just the tip of the iceberg, because these numbers correspond many other invisible visible, involving: minor injuries that do not require health care and are not reported, or those that remain hidden because of cultural patterns or the links between victim and perpetrator - as is the case of domestic violence. Violence against women occurs worldwide, and is a phenomenon that affects women of different social classes, origins, marital status, educational level or race. Women experience throughout their lives, various types of violence and abuse, such as verbal aggression type, physical and sexual, which may be committed by a partner or ex-partner, family, acquaintances or strangers. The consequences of violence suffered by women embody in disorders biological, psychological, moral and social, making it difficult for women to experience human equality and social in full. Much of the violence against women is perpetrated by intimate partners, this is defined as behavior within an intimate relationship that causes physical, sexual or psychological harm, including acts of physical aggression, sexual coercion, psychological abuse and intimidating behaviors. Due to the nature of intimate partner violence, the occurrence and impacts are subestimados. O present study is nested in research "Program Health Promotion and Violence Prevention in Primary Care" coordinated by the Center for Health and Peace, the Department of Social and Preventive Medicine, Federal University of Minas Gerais, held in Ribeirão das Neves, metropolitan region of Belo Horizonte, Minas Gerais, Brazil, in July 2012. We interviewed 954 individuals, professionals and users of primary health care that county. Data collection occurred through the application of semi-structured questionnaire. Data were coded and typed with double entry and analyzed using SPSS software. The object of this study was women users of Primary Health Care, recruited from 53 Basic Health Units and 5 Units Basic Reference existing in this municipality. The methodological approach chosen was a quantitative and representative sample of 470 women (calculated with 5% error). Tests were chi-square and ratio chances. Optou by the presentation of the final form of two articles I) Violence against women caused by intimate partner, underwent Femina magazine and is a review article of the literature on the types of violence against women, focusing on the violence provoked by the partner íntimo. II) caused by intimate partner violence: prevalence and associated factors among users of primary health care in the metropolitan region of Belo Horizonte, Minas Gerais, Brazil which will be submitted later. In it are presented the results and analysis of the interviews conducted in the research field. This research aimed to investigate the occurrence of violence against women, specifically caused by intimate partner violence; characterize its dimensions: physical violence, verbal / moral / psychological and sexual, a profile of women victims and investigate whether there are risk factors for violence. The results pointed to a sad reality where a significant number of women are victims of violence caused by their partners. Factors such as low education, age, health problems and migraines are risk factors for violence. The findings confirm previous studies regarding the magnitude and overlapping of intimate partner violence.